Peran Layanan Bimbingan Karir bagi Siswa dengan Keterbelakangan Mental: Studi Fenomenologi - Yuliani Pertiwi; Asniti Karni; Hermi Pasmawati (Indonesian Journal of Guidance and Counseling Studies, 2025)
Background: Every parent expects the presence of a child, ideally one who is perfect and without shortcomings. However, the reality is that some children are born with disabilities, which requires special attention in their development, especially in preparing them for future careers. Objective: This study aims to determine the role of SMALB (Sekolah Menengah Atas Luar Biasa) in Bengkulu City in providing career guidance services to students with disabilities. Method: The research utilized a qualitative method with a phenomenological approach to deeply understand the lived experiences of students. The study was conducted at Sekolah Luar Biasa Negeri (SLBN) 01 Bengkulu City in 2022. Fourteen students participated as research subjects. Data were collected through observation, interviews, and documentation. The data were analyzed using the interactive model of Miles & Huberman, which includes data reduction, data display, and conclusion drawing/verification. Result: The findings revealed that career guidance at the SMALB level in SLBN 01 Bengkulu City was conducted using an individualized approach tailored to each student's needs. The demonstration method was predominantly applied, and the overall guidance process was instructive in nature, emphasizing practical skills and one-on-one instruction to facilitate learning and development. Conclusion: Career guidance at SLBN 01 Bengkulu City emphasizes inclusive, personalized support to empower students with disabilities in pursuing careers that match their abilities and interests. Contribution: his study enriches limited research on career guidance for students with disabilities in Indonesia, highlighting the value of individualized approaches and offering insights for improving inclusive education policies and practices.